Esprit De Corps Mediates The Influence Of Participative Leadership And Employee Engagement On Employee Performance: Case Study In A Healthcare Company - Fariha Azzahra; Winarsih Winarsih; Wahyu Hermawan (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze how the influence of participative leadership and employee engagement on esprit de corps and analyze the influence of participative leadership and employee engagement on employee performance through esprit de corps. the population in this study amounted to 358 respondents. the research sample used the slovin formula with random sampling technique so that a sample of 189 nurses was obtained at rsud dr. r. soedjati soemoediardjo purwodadi grobogan. analysis techniques using structural equation modeling (sem) amos 22. the results showed that participative leadership and employee engagement had a significant positive effect on esprit de corps, participative leadership had a significant positive effect on employee erformance and esprit de corps mediated participative leadership on employee performance and employee engagement on employee performance. further research can add research variables to better understand the factors that improve nurse performance in hospitals.